Differences in rates and odds for emergency caesarean section in six Palestinian hospitals: a population-based birth cohort study. Issue 3 (2nd March 2018) - Zimmo, Mohammed; Laine, Katariina; Hassan, Sahar; Fosse, Erik; Lieng, Marit; Ali-Masri, Hadil; Zimmo, Kaled; Anti, Marit; Bottcher, Bettina; Sørum Falk, Ragnhild; Vikanes, Åse
Abstract : Objective: To assess the differences in rates and odds for emergency caesarean section among singleton pregnancies in six governmental Palestinian hospitals. Design: A prospective population-based birth cohort study. Setting: Obstetric departments in six governmental Palestinian hospitals. Participants: 32 321 women scheduled to deliver vaginally from 1 March 2015 until 29 February 2016. Methods: To assess differences in sociodemographic and antenatal obstetric characteristics by hospital, χ 2 test, analysis of variance and Kruskal-Wallis test were applied. Logistic regression was used to estimate differences in odds for emergency caesarean section, and ORs with 95% CIs were assessed. Main outcome measures: The primary outcome was the adjusted ORs of emergency caesarean section among singleton pregnancies for five Palestinian hospitals as compared with the reference (Hospital 1). Results: The prevalence of emergency caesarean section varied across hospitals, ranging from 5.8% to 22.6% among primiparous women and between 4.8% and 13.1% among parous women. Compared with the reference hospital, the ORs for emergency caesarean section were increased in all other hospitals, crude ORs ranging from 1.95 (95% CI 1.42 to 2.67) to 4.75 (95% CI 3.49 to 6.46) among primiparous women. For parous women, these differences were less pronounced, crude ORs ranging from 1.37 (95% CI 1.13 to 1.67) to 2.99 (95% CI 2.44 to 3.65). After adjustment for potential confounders, the ORs were reduced but still statistically significant, except for one hospital among parous women. Conclusion: Substantial differences in odds for emergency caesarean section between the six Palestinian governmental hospitals were observed. These could not be explained by the studied sociodemographic or antenatal obstetric characteristics.